Getting started with LLVM core libraries : get to grips with LLVM essentials and use the core libraries to build advanced tools /: get to grips with LLVM essentials and use the core libraries to build advanced tools. (2014) - Lopes, Bruno Cardoso; Auler, Rafael
No abstract available